A first principles theory of nuclear magnetic resonance J-coupling in solid-state systems. - Joyce, SA; Yates, JR; Pickard, C; Mauri, F (2007)
A method to calculate NMR J-coupling constants from first principles in extended systems is presented. It is based on density functional theory and is formulated within a planewave-pseudopotential framework. The all-electron properties are recovered using the projector augmented wave approach. The method is validated by comparison with existing quantum chemical calculations of solution-state systems and with experimental data. The approach has also been applied to the silicophosphate, Si(5)O(PO(4))(6), giving (31)P-(29)Si-couplings which are in excellent agreement with experiment.